Feeling betrayed the roots of Muslim anger at America - Kull, Steven (Brookings Institution Press, 2011)
"Explores the depth of anti-Americanism felt by Muslim populations in the Middle East and South Asia by reporting on opinions expressed during focus group sessions and in-depth surveys over several years, complemented by data from Gallup polls, World Values Survey, and Arab Barometer"--Provided by publisher.